PENGARUH PERSEPSI KEADILAN PAJAK DALAM PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN DALAM MEMENUHI KEWAJIBAN PERPAJAKAN - Soliyah Wulandari; Andrie Budiaji (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2018)
The purpose of this research is to analyze the influence of perceptions of tax fairness towards compliance in fulfilling taxation of obligations. Azmi and Perumal (2008) identified five of tax fairness dimension: general fairness, exchanges with government, special provisions, tax rates, and self-interest towards individual taxpayers compliance.This research used primary data obtained by distributing questionnaire to micro and small business owners in Center of Promotion and Marketing Horticultural Department of Marine and Agriculture DKI Jakarta. Multiple regression analysis was used to identify dimensions of tax fairness that influence compliance in fulfilling taxation obligations.The results of this research indicate that general fairness and the structure of tax rates influence towards compliance of micro and small businesses in fulfilling taxation obligations, while exchange with government, special provisions, and self-interest does not influence towards compliance of micro and small businesses in fulfilling taxation obligations.